The Potential of Cassava Peel Waste as a Material of Biodegradable Plastic using Calcium Silicate Filler - Noor Isnaini Azkiya; S. Sigit Udjiana; Arya Rizqy Irangga; Anatasya Tania Febiyanti (Politeknik Negeri Malang, 2023)
Biodegradable plastics are plastics that can be degraded and decomposed quickly by microorganisms in the soil. In this study, biodegradable plastic was made with starch from cassava peel waste, sorbitol as a plasticizer, and calcium silicate as a filler. This research was conducted to determine the effect of the amount of filler and the amount of plasticizer on biodegradation properties, tensile and elongation strength, and water absorption properties. The variables used in the plasticizer are 30%, 40%, and 50% (w/w) of the weight of cassava peel starch. While the variables used for filler are 1%, 3%, 5%, and 7% (w/w) of the weight of cassava peel starch. The results of the study showed that the highest biodegradation test results were 81.7% with 7% calcium silicate filler variables and 50% plasticizer sorbitol, tensile strength test obtained the highest value of 0.767 MPa on 3% calcium silicate filler variables and 30% sorbitol, elongation test with the highest value on the filler variable calcium silicate 7% and sorbitol 30% that is equal to 5.20% and the water adsorption test obtained the smallest value is 10.33% on the filler variable calcium silicate 1% and sorbitol 30%. The biodegradable plastic as a result of this research has met the standards for degradation ability based on the ASTM 6400 standard but has not met the standards for tensile strength, elongation, and water adsorption.